Drug Testing and Community Supervision Outcomes. (April 2020) - Hicks, William D.; Holcomb, Jefferson E.; Alexander, Melissa A.; Clodfelter, Tammatha A.
The requirement to submit to drug testing is either a standard or special condition of adult community correctional supervision in most jurisdictions. Positive drug test results are one of the most common violations of probation that result in official action by a supervising officer. This study examines the relationship between individual characteristics, drug test results, and federal supervision outcomes. Results indicate that individual risk score and offense category are associated with positive drug tests. Furthermore, testing positive for hard drugs is associated with revocation for new crimes and non-drug technical violations, but testing positive for cannabis only is not associated with supervision revocation for either reason.